2020
DOI: 10.1186/s12885-020-07180-x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of dual CAR-T targeting PDL1 and MUC16 antigens on ovarian cancer cells in mice

Abstract: Background: More favorable treatment against epithelial ovarian cancer (EOC) is urgently needed because of its insidious nature at an early stage and a low rate of five-year survival. The current primary treatment, extensive surgery combined with chemotherapy, exhibits limited benefits for improving prognosis. Chimeric antigen receptor T (CAR-T) cell technology as novel immunotherapy has made breakthrough progress in the treatment of hematologic malignancies, and there were also benefits shown in a partial sol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 41 publications
0
34
0
1
Order By: Relevance
“…Isoforms of MUC16 have also been implicated in the progression and metastasis of pancreatic ductal adenocarcinoma as well as aggressive subtypes of the disease such as squamous and basal-like carcinomas (9,10). Despite its endogenous expression in a few healthy tissues and status as a shed antigen, MUC16 remains a viable therapeutic target for antibody-based and adoptive cell therapies (11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Isoforms of MUC16 have also been implicated in the progression and metastasis of pancreatic ductal adenocarcinoma as well as aggressive subtypes of the disease such as squamous and basal-like carcinomas (9,10). Despite its endogenous expression in a few healthy tissues and status as a shed antigen, MUC16 remains a viable therapeutic target for antibody-based and adoptive cell therapies (11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies have shown that targeting overexpressed molecules like mucin 16 (MUC16), annexin 2 (ANXA2), and also HER2 can sustain high tumor cells toxicity, and so dwindle tumor burden [ 134 ]. For instance, MUC16-redirected CAR T cells exhibited a therapeutic benefit versus human breast OVCAR-3 tumor-bearing mice and also prolonged their survival time [ 135 ]. Notwithstanding, because of the inherent heterogeneity of OC concurrently high mutation multiplicity and overexpression of diverse receptors, employing individual therapeutic strategies is largely desired [ 134 ].…”
Section: Her2-specific Cars In Human Tumor Therapymentioning
confidence: 99%
“…To overcome ‘on-target off-tumour’ cytotoxicity, the dual-target CARs may be a better choice [ 92 ]. It has been shown that dual CARs are related to the longer survival time of mice up to two times when compared to single CAR groups and control group (80 vs. 40 days) [ 83 ].…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 99%
“…MUC16-CAR-T cells injected intravenously or intraperitoneally are able to delay OC’s progression or altogether remove tumours in mouse tumour-bearing models. Therefore, again it seems that MUC16 is an ideal antigenic target for CAR molecules [ 83 ].…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 99%